Estrutura e dinâmica de perfilhamento do capim-marandu com alturas variáveis no inverno - Costa, Ludiêmilem Keith Parreira da (2016)
The livestock system in Brazil mainly uses the pastures as source of food to cattle, and the marandu palisade grass is one of the main forage crop plants. In order to supply the demand of these animals in amount of forage, it is necessary to adopt management strategies aimed at increased forage production with adequate characteristics to animal intake. In this context, is requiered to identify management strategies of defoliation that improve tillering of marandu palisade grass during the seasons. There is a chance that the maintenance of lower marandu palisade grass during the fall and winter compared to spring and summer, increase the incidence of light at the base of the plants and, indeed, encourage tillering and modify the structure of the pasture compared to maintain marandu palisade grass with constant height along these stations.